Hydrate-based carbon capture process: assessment of various packed bed systems for boosted kinetics of hydrate formation - Arora, Amit; Kumar, Asheesh; Bhattacharjee, Gaurav; Balomajumder, Chandrajit; Kumar, Pushpendra (Journal of Energy Resources Technology-Transactions of the ASME, 2021)
The case for developing novel technologies for carbon dioxide (CO2) capture is fast gaining traction owing to increasing levels of anthropogenic CO2 being emitted into the atmosphere. Here, we have studied the hydrate-based carbon dioxide capture and separation process from a fundamental viewpoint by exploring the use of various packed bed media to enhance the kinetics of hydrate formation using pure CO2 as the hydrate former. We established the fixed bed reactor (FBR) configuration as a superior option over the commonly used stirred tank reactor (STR) setups typically used for hydrate formation studies by showing enhanced hydrate formation kinetics using the former. For the various packing material studied, we have observed silica gel with 100 nm pore size to return the best kinetic performance, corresponding to a water to hydrate conversion of 28 mol% for 3 h of hydrate growth. The fundamental results obtained in the present study set up a solid foundation for follow-up works with a more applied perspective and should be of interest to researchers working in the carbon dioxide capture and storage and gas hydrate fields alike.
Keywords: air emissions from fossil fuel combustion; Carbon dioxide capture; combustion of waste; Fixed bed reactor; fuel combustion; Gas hydrate; hydrates; kinetics; Silica gel